The Impact of Running at Night on Physical Fitness: Dampak Lari pada Malam Hari terhadap Kebugaran Jasmani - Kartono; Ricky Ferrari Valentino Ward; Randy Achmad Nurzenis (Journal of Physical and Outdoor Education, 2022)
This study aims to determine the impact of running at night on physical fitness. This research uses experimental research with a one shot case study design. The sample in this study was the wall climbing community of Saparua Bandung. Based on the results of the data, it can be concluded that there is a significant effect of running at night on physical fitness. The results of this study indicate that members of Wall Climbing Saparua Bandung have 0% members with poor fitness levels, 1% in the poor category, 25% members in the moderate category, 65% members in the good category, and 5% members in the poor category. excellent level of physical fitness. So it can be concluded that the members of the Wall Climbing Saparua Bandung community have a good level of physical fitness